DEVELOPMENT OF BASIC TECHNIQUES PROCUREMENT MODEL A BOL SOCCER ATHLETES BASED PLAY FOR BEGINNERS AGES 8-12 YEARS - Ahmad Atiq; James Tangkudung; Mulyana Mulyana (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
The research aimed to develop basic technique drill using Play- based training for beginner athletes in the age of 8-12 years old in football schools in Universitas Diponegoro and Djarum Kudus. The research employed Borg and Gall methodology by three treatments; namely small group test, big group test, and model test. Research finding showed that in small group test this model could be applied for beginner athletes, while in big group this model was able to be used with coach instruction and in model test there was significant improvement on basic technique drill on passing, dribbling, heading, and shooting. Based on model test (t test), pre -test was 10,69 and post-test was 10,91 with average score was 10,80 increasing by 98%. It can be suggested game based training could improve passing, trapping, dribbling, heading and shooting techniques. Key words: Developing, Play-Based Training, Technique Drill